2014
DOI: 10.1089/dia.2013.0253
|View full text |Cite
|
Sign up to set email alerts
|

A Multicenter, Prospective, Randomized, Double-Blind Study to Evaluate the Safety and Efficacy of Saroglitazar 2 and 4 mg Compared with Placebo in Type 2 Diabetes Mellitus Patients Having Hypertriglyceridemia Not Controlled with Atorvastatin Therapy (PRESS VI)

Abstract: Background: Dyslipidemia due to diabetes is characterized by hypertriglyceridemia and reduced levels of high-density lipoprotein cholesterol (HDL-C) and elevated or normal levels of low-density lipoprotein cholesterol (LDL-C) in type 2 diabetes mellitus (T2DM). The objectives of this Phase III study were to evaluate the safety, tolerability, and efficacy of saroglitazar (ZYH1) 2-mg and 4-mg tablets (LipaglynÔ; Zydus Cadila, Ahmedabad, India) compared with placebo in patients with diabetic dyslipidemia who are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
118
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(120 citation statements)
references
References 16 publications
2
118
0
Order By: Relevance
“…The remarkable improvement in mitochondrial FAO and insulin-mediated glucose uptake in myotubes by fenofibrate observed in our study is not replicated to a similar extent in clinical practice, possibly because of a much lower dose are used in human subjects due to safety concerns. A more potent and a safer PPARα agonist, like saroglitazar, may be the answer to palmitate induced lipotoxicity and insulin resistance in skeletal muscles in human subject with type2 diabetes in future [51,52].…”
Section: Discussionmentioning
confidence: 99%
“…The remarkable improvement in mitochondrial FAO and insulin-mediated glucose uptake in myotubes by fenofibrate observed in our study is not replicated to a similar extent in clinical practice, possibly because of a much lower dose are used in human subjects due to safety concerns. A more potent and a safer PPARα agonist, like saroglitazar, may be the answer to palmitate induced lipotoxicity and insulin resistance in skeletal muscles in human subject with type2 diabetes in future [51,52].…”
Section: Discussionmentioning
confidence: 99%
“…Both the saroglitazar arms (saroglitazar 2 mg/day + atorvastatin and saroglitazar 4 mg/day + atorvastatin) showed significant reduction in triglycerides (-45.5 ± 3.03% and -46.7±3.02% respectively in 2 mg and 4 mg arms) as compared with the third control arm (placebo + atorvastatin). 23 There was a significant decrease in levels of non-HDL-C, very LDL-C, total cholesterol and FPG in saroglitazar 2 mg arm while an additional decrease in LDL-C and apolipoprotein B levels was also observed in saroglitazar 4 mg arm. A reduction in HbA1 c level was also observed in both the saroglitazar arms but it was considered non-significant statistically.…”
mentioning
confidence: 83%
“…29 In another multicenter study to evaluate the efficacy and safety of different doses of saroglitazar versus placebo (PRESS VI), gastritis was reported to be most common adverse effect. 30 These studies did not provide any possible explanation of association of gastritis or fatigue with saroglitazar use but reported that the ADRs due to saroglitazar were mild to moderate in intensity. Our findings are similar to these studies.…”
Section: Ppar α/γ Agonistmentioning
confidence: 96%
“…There has been a 46.7% decrease in trigltcerides, 32.5% decrease in non-HDL-C, 0.3% absolute reduction in glycosylated hemoglobin (HbA1c). 13,14 With increasing cases of lifestyle disorders along with diabetic dyslipidemia, saroglitazar is bound to help several patients suffering from it. Simultaneous agonistic activity on PPAR-α and PPAR-γ is a novel treatment option for diabetic dyslipidemia and other such discoveries in this area shall benefit many.…”
Section: Peroxisome Proliferator Activated Receptor (Ppar)-α/γ Agonistmentioning
confidence: 99%